The Utilization of Artificial Intelligence in Scientific Writing Education - Kusmanto, Hari; Sohnui, Suhailee; Sari, Essa Rohimah; Mujiani, Ika (Educative: Jurnal Ilmiah Pendidikan, 2025)
Scientific writing is an essential skill for students in completing their studies. However, many students face challenges in academic writing. The integration of Artificial Intelligence (AI) in learning scientific writing is becoming increasingly important. This article aims to explore the domain of AI in scientific writing education. The method used in this research is a systematic review of Scopus databases published from 2020 to 2024. This study focuses on the application of AI in scientific writing education. The review identified 29 studies on AI implementation in scientific writing learning, encompassing: 1) real-time guidance and feedback, 2) development of writing skills and adaptive learning, 3) writing efficiency and productivity, 4) inspiration and reference resources, 5) analysis of writing quality and data, 6) development of critical thinking and digital literacy, 7) personalized learning and access to information, 8) reference resources and self-study, and 9) collaboration and interaction in the writing process. AI is significantly utilized across various domains in scientific writing education. However, the use of AI in this context should consider ethical aspects. Further research and development are crucial to address emerging challenges and ethical considerations.